Current approaches to the technology of bakery products made from frozen prepared food - Rohliev, Iosif; Havrysh, Andrey; Dotsenko, Viktor; Lukianets, Halyna (My University, 2013)
In recent years the technology of bakery products that uses freezing is developing rapidly in most developed countries, including Western European and Northern American ones. New technology of using frozen bakery production allows responding to market needs in supplying fresh products in a wide range to the population, and managing the quality and safety of frozen dough products on the stage of their preparation.
Keywords: freezing; заморожування; замораживания; dough; тісто; тесто; yeast cells; дріжджові клітини; дрожжевые клетки; sugar; цукор; сахар; egg yolk; яєчний жовток; яичный желток; lecithin; лецитин; кафедра іноземних мов професійного спрямування; кафедра готельно-ресторанної справи